The association between sociodemographic and clinical factors and outcomes among inpatients with community‐acquired pneumonia - Farhana Islam; Surain B. Roberts; Sarah L. Malecki; Anne Loffler; Leo Hersi; Anthony D. Bai; Amol A. Verma; Fahad Razak; Peter J. Gill; Sanjay Mahant (Journal of Hospital Medicine, 2026)
Abstract Background Community‐acquired pneumonia (CAP) is a leading cause of hospitalization and mortality. The influence of sociodemographic characteristics on adverse outcomes in adults hospitalized with CAP remains poorly understood, particularly for patients younger than 65. Objectives To evaluate associations between baseline sociodemographic characteristics and a composite outcome of intensive care unit (ICU) admission or in‐hospital mortality, and whether these differed across age strata (18–39, 40–64, and ≥65 years). Methods We conducted a multicentre, retrospective, cohort study of adults ≥18 years hospitalized with CAP between 2015 and 2024 in Ontario. Using generalized linear mixed models stratified by age, we evaluated the adjusted effects of clinical (i.e., comorbidity and illness severity) and sociodemographic characteristics (i.e., age, sex, four dimensions of neighborhood‐level marginalization) with the composite outcome. We compared the contribution to model fit of these variable groups using nested likelihood ratio tests. Results Among 84,356 hospitalizations, males had higher adjusted odds of the composite outcome across all age groups (adjusted odds ratio [aOR] range: 1.25–1.48), while residence in areas with higher concentrations of racialized/newcomer populations was associated with lower odds of the composite outcome (aOR range: 0.89–0.96). Nested likelihood ratio tests showed that clinical characteristics contributed substantially more to outcome variation than sociodemographic factors (χ 2 1682 vs. 145 in the ≥65 stratum). Conclusions Sociodemographic and clinical characteristics were associated with severe CAP outcomes, but clinical factors accounted for a greater proportion of outcome variation. Incorporating sociodemographic information, including sex, age, and marginalization measures, into early assessment may improve identification of patients at higher risk.